2020
DOI: 10.1016/s1473-3099(20)30021-9
|View full text |Cite
|
Sign up to set email alerts
|

Researching Zika in pregnancy: lessons for global preparedness

Abstract: Our understanding of congenital infections is based on prospective studies of women infected in pregnancy. The European Union has funded three consortia to study Zika virus (ZIKV), each including a prospective study of pregnant women. Another has been funded by National Institutes of Health. This personal view sets out the study designs required to research ZIKV, and questions whether funding academics in the EU and US to work with collaborators in outbreak areas is an effective strategy. Three years after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…We included prospective studies of women with Zika virus infection in pregnancy reporting adverse pregnancy and birth outcomes, markers of congenital infection, or both, based on a previous analysis and review of alternative designs for prospective studies of Zika virus in pregnancy. 10 All the seven studies known to the authors…”
Section: Study Identification and Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…We included prospective studies of women with Zika virus infection in pregnancy reporting adverse pregnancy and birth outcomes, markers of congenital infection, or both, based on a previous analysis and review of alternative designs for prospective studies of Zika virus in pregnancy. 10 All the seven studies known to the authors…”
Section: Study Identification and Data Extractionmentioning
confidence: 99%
“…In the absence of accurate diagnostic tests for congenital infection, inferences about the causal role of Zika virus in adverse pregnancy out comes therefore require a second maternal control group of infants born to women who have not had a Zika virus infection during pregnancy. 10 However, Zika virus poses further difficulties: although PCR testing in pregnancy is a highly specific indicator of infection, even the most intensive PCR testing protocol is likely to miss Zika virus infections because of the short duration of the PCR response, perhaps as short as 7 days. 11 Seroconversion, IgG3, or IgM testing can identify infection in pregnancy, but lack specificity because of crossreaction with other flaviviruses, and may only reflect an infection that cleared before pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is still growing with respect to vertical transmission of ZIKV, which has been challenging to investigate due to factors including the high proportion of asymptomatic infections in pregnant women and challenges around testing and interpretation of potential laboratory markers of infection. 28 , 29 A recent analysis using published data from 7 studies with prospective data on ZIKV in pregnancy provided preliminary estimates of average vertical transmission rates by trimester, respectively 47%, 28%, and 25% in the first, second and third trimesters. 30 This same analysis estimated that probability of an infant having CZS symptoms was 9% following maternal ZIKV infection in the first trimester, and 3% and 1%, respectively where the mother was infected in the second and third trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…During the worldwide Zika outbreak between 2013 and 2016, it was demonstrated that intrauterine ZIKV infection is associated with microcephaly, as well as a wide range of congenital anomalies characterizing congenital Zika syndrome (CZS) (Ades et al, 2020;Moore et al, 2017;Petersen et al, 2016). In Southeast Asia, despite the evidence of long-term, but low-level, circulation of ZIKV (Kuadkitkan et al, 2020;Lim et al, 2017;Petersen et al, 2016), few cases of CZS have been reported in Vietnam and Thailand (Figure 1) (Kuadkitkan et al, 2020;Moi et al, 2017;Wongsurawat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%